Hippocampal Dysfunction in Schizophrenia and Aberrant Hippocampal Synaptic Plasticity in Rodent Model Psychosis: a Selective Review - Bartsch, Julia C.; Schott, Björn H.; Behr, Joachim (Pharmacopsychiatry, 2019)
Schizophrenia is a complex, heterogeneous psychiatric disorder that affects about 1% of the global population. Hippocampal dysfunction has been linked to both cognitive deficits and positive symptoms in schizophrenia. Here, we briefly review current findings on disrupted hippocampal processing from a clinical perspective before concentrating on preclinical studies of aberrant hippocampal synaptic plasticity using the N-methyl-D-aspartate receptor hypofunction model of psychosis and related findings from genetic models. Taken together, the results put the case for maladaptive hippocampal synaptic plasticity and its extrinsic connections as mechanistic underpinnings of cognitive impairments in schizophrenia.
Keywords: schizophrenia; hippocampus; synaptic plasticity; dopamine; long-term potentiation